Larangan dan Sanksi Tindak Pidana Kekerasan Seksual Dalam Rumah Tangga (Studi Komparasi Hukum Islam dan Undang-undang Nomor 23 Tahun 2004 tentang Penghapusan Kekerasan Dalam Rumah Tangga) - Ardiansyah, Ardiansyah (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2016)
The prohibition and sanction criminal acts of sexual violence in the household, according to Law No. 23 of 2004 on the Elimination of Domestic Violence and Islamic law. This research is motivated by the issue of a deviant sexual towards his wife, where problems in the private sphere has been appointed to the public domain through which no detailed PKDRT Regulation explains the term forcing sexual intercourse as a form of violence. Approach legislation, conceptual, philosophical and juridical comparison is used to analyze the prohibition and sanction criminal acts of violence. Islamic law explains that sexual violence against wives are despicable acts and prohibited. Islam considers sexual violence than because the two sides (husband and wife). Meanwhile, the perpetrators of criminal sanctions can be sanctioned as jarimah ta’zir. Meanwhile, according to Law PKDRT that each act of sexual violence or similar coercive sexual relations are prohibited. The sanction is imprisonment or a fine. The second equation of the law is equally considers the act contains harm or evil. Meanwhile, the difference is that in Islamic law to first see the cause and effect of violence, both in terms of the condition of both husband and wife. Meanwhile, the Law PKDRT otherwise. Differences were also found in the penal provisions. In Islamic law, perpetrators can be sanctioned jarimah ta’zir where possible occurrence of sanctions mildest to the most severe. Meanwhile, in the Act PKDRT there is no a minimal set of sanctions so that it is possible for the victims of injustice.